Elevated Neutrophil Lymphocyte Ratio in Recurrent Optic Neuritis - Hande Guclu; Sadık Altan Ozal; Vuslat Pelitli Gurlu; Ramazan Birgul (Journal of Ophthalmology)
Purpose. To demonstrate the relation between optic neuritis (ON) and systemic inflammation markers as neutrophil lymphocyte ratio (N/L ratio), platelet count, mean platelet volume (MPV), and red cell distribution width (RDW) and furthermore to evaluate the utilization of these markers to predict the frequency of the ON episodes. Methods. Forty-two patients with acute ON and forty healthy subjects were enrolled into the study. The medical records were reviewed for age, sex, hemoglobin (Hb), Haematocrit (Htc), RDW, platelet count, MPV, white blood cell count (WBC), neutrophil and lymphocyte count, and neutrophil lymphocyte ratio (N/L ratio). Results. The mean N/L ratio, platelet counts, and RDW were significantly higher in ON group (p=0.000, p=0.048, and p=0.002). There was a significant relation between N/L ratio and number of episodes (r=0.492, p=0.001). There was a statistically significant difference for MPV between one episode group and recurrent ON group (p=0.035). Conclusions. Simple and inexpensive laboratory methods could help us show systemic inflammation and monitor ON patients. Higher N/L ratio can be a useful marker for predicting recurrent attacks.